A case study on internet adoption among rural communities in Sri Lanka - G.T. Madhubhashini Galagedara; Ali Salman; Wan Amizah Wan Mahmud; Fauziah Ahmad (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2014)
Sri Lankan internet user percentage has lingered at a mere 18.3% according to World Bank Report, 2013. The aim of this paper is to identify the issues hindering Internet adoption among rural communities in Sri Lanka. This paper also will report results of correlation analysis regarding the relationship between Internet adoption and infrastructural facilities, adopter characteristics of rural communities, technology characteristics and affordability. A survey using questionnaire was used to obtain data from 400 respondents in Bibile, Monaragala district. The data was analysed using the Statistical Package for Social Sciences (SPSS version 20.0). From the correlation analysis all the nine variables have strong significant relationship with Internet adoption. There is a strong significant negative relationship between Internet adoption and infrastructural facilities, computer skills and affordability. The results show that Internet adoption among the rural communities was low due to lack of infrastructural facilities, problem of affordability and low in computer skills. Therefore, the government and non-government organizations should introduce ICT policies, infrastructural facilities and effective Island wide projects to change the attitudes and behavior of the rural communities in Sri Lanka. With proper infrastructure, better financial backing, English language skills and computer skills, the rural communities can easily connect to the internet for their development activities. Therefore this study suggests that attention should be given to the variable having effects on internet adoption among the rural communities in Sri Lanka.